2015
DOI: 10.1007/s11249-015-0510-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Grooves on the Static Friction of an Elastic Slider

Abstract: Numerous studies have proved the usefulness of surface patterning for the modification of tribological performances of sliding contacts. Here we investigate the effects of patterning on the tribological properties of a slider over a solid substrate. We show that, depending on the numerical density of surface grooves, the tribological properties can change significantly. A low density of surface patterning leads to a decrease of static friction force, while a higher density weakens this effect. The decrease is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 26 publications
3
20
0
1
Order By: Relevance
“…We start with a periodic regular succession of grooves and pawls. This pattern has already been studied both experimentally [20,21] and numerically with a slightly different model [34]. Our aim is therefore to first obtain known results so as to validate the model.…”
Section: A First-level Patterningmentioning
confidence: 91%
See 1 more Smart Citation
“…We start with a periodic regular succession of grooves and pawls. This pattern has already been studied both experimentally [20,21] and numerically with a slightly different model [34]. Our aim is therefore to first obtain known results so as to validate the model.…”
Section: A First-level Patterningmentioning
confidence: 91%
“…This model was first introduced by Burridge and Knopoff [22] in the study of the elastic deformation of tectonic plates. Despite its simplicity, the model is still used not only in this field [23][24][25], but also to investigate some aspects of dry friction on elastic surfaces, e.g., the static to dynamic friction transition [26][27][28][29][30], stick-slip behavior [31][32][33], and the role of regular patterning [34].…”
Section: Modelmentioning
confidence: 99%
“…One of the most widely used models is the one dimensional spring-block model, which was originally introduced to study earthquakes [29]- [31] and has also been used to investigate many aspects of dry friction of elastic materials [32]- [39]. In [40] we have extensively investigated the general behavior of the model and the effects of local patterning (regular and hierarchical) on the macroscopic friction coefficients, and in [41] we have extended the study to composite surfaces, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The structure considered in figure 3 is similar to a patterned surface with grooves, in which the friction coefficient is assumed to be zero. In this case, it is known both from numerical studies [7] and experimental results [41][42] that static friction decreases with the width of the grooves. In our previous work [10] we have also shown that this is due to the increase of the shear stress concentrations at the edge of the grooves.…”
Section: Friction On Variable-roughness Patterned Surfacesmentioning
confidence: 99%
“…grooves and pawls perpendicular to the direction of motion. The effects of these structures have been studied both numerically [7] and experimentally [8] [9], and recently their hierarchical arrangement has also been investigated by means of numerical simulations [10]: results show that by changing the architecture of the contact surface only, the global static friction coefficients can be tuned without changing the chemical or physical properties of the material. This is because by exploiting patterning it is possible to modify mesoscopic features, i.e.…”
Section: Introductionmentioning
confidence: 99%